2022
DOI: 10.1192/bjp.2022.24
|View full text |Cite
|
Sign up to set email alerts
|

Clozapine-induced gastrointestinal hypomotility: presenting features and outcomes, UK pharmacovigilance reports, 1992–2017

Abstract: Background Clozapine-induced gastrointestinal hypomotility (CIGH) affects some 75% of patients treated with clozapine. Aims To document the incidence of potentially harmful CIGH in the UK. Method We studied spontaneous UK pharmacovigilance reports recorded as clozapine-related gastrointestinal adverse drug reactions, 1992–2017. Results There were 527 patients reported with potentially harmful CIGH; 33% (n = 172) died. Deaths averaged 1 per year 1992–19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…The first 4 panels of Supplementary Table 13 (in the onlineonly Data Supplement) provide information that the author has gathered on the use of clozapine in the UK; the emphases are on guidelines, 39,127,159,160 the contribution of clozapine-induced agranulocytosis, 70,[161][162][163] what is known of UK fatal outcomes of clozapine-induced myocarditis, 67,104,164 clozapine-induced CIGH, 165 and clozapine-associated pneumonia. 166 Two months ago, the author' s understanding of clozapine use in the UK was completely shaken by discovering a VigiBase pharmacovigilance study focused on ADRs with fatal outcomes reported by physicians.…”
Section: High Lethality In Uk Clozapine Patients Is Puzzlingmentioning
confidence: 99%
“…The first 4 panels of Supplementary Table 13 (in the onlineonly Data Supplement) provide information that the author has gathered on the use of clozapine in the UK; the emphases are on guidelines, 39,127,159,160 the contribution of clozapine-induced agranulocytosis, 70,[161][162][163] what is known of UK fatal outcomes of clozapine-induced myocarditis, 67,104,164 clozapine-induced CIGH, 165 and clozapine-associated pneumonia. 166 Two months ago, the author' s understanding of clozapine use in the UK was completely shaken by discovering a VigiBase pharmacovigilance study focused on ADRs with fatal outcomes reported by physicians.…”
Section: High Lethality In Uk Clozapine Patients Is Puzzlingmentioning
confidence: 99%
“…There is insufficient trial-based evidence to compare the effectiveness and safety of common laxatives for clozapine-induced constipation [4]. The risk of serious morbidity/mortality from clozapine-associated constipation is substantial, and there is a need for active monitoring of bowel function [5]. Due to the potential severity of clozapine-induced constipation, coadministration of laxatives is frequently encountered in clinical care [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The risk of serious morbidity/mortality from clozapine-associated constipation is substantial, and there is a need for active monitoring of bowel function [5]. Due to the potential severity of clozapine-induced constipation, coadministration of laxatives is frequently encountered in clinical care [5,6]. Lubiprostone is currently approved by FDA for treatment of opioid-induced constipation, irritable bowel syndrome with constipation, and chronic idiopathic constipation.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, UK reports from all sources indicated 383 mean clozapine fatal outcomes every year (3828 in the last 10 years). 10…”
mentioning
confidence: 99%